Nucleoporins cooperate with Polycomb silencers to promote transcriptional repression and repair at DNA double-strand breaks - Hongseon Song; Yubin Bae; Sangin Kim; Dante Deascanis; Yujin Lee; Gergely Rona; Ethan Lane; Seo-yeoung Lee; Su-Jung Kim; Michele Pagano; Kyungjae Myung; Younghoon Kee (Proceedings of the National Academy of Sciences, 2025)
DNA double-strand breaks (DSBs) are harmful lesions and major sources of genomic instability. Studies have suggested that DSBs induce local transcriptional silencing that consequently promotes genomic stability. Several factors have been proposed to actively participate in this process, including Ataxia-telangiectasia mutated (ATM) and Polycomb repressive complex 1 (PRC1). Here, we found that disrupting PRC1 clustering disrupts DSB-induced gene silencing. Interactome analysis of PHC2, a PRC1 subunit that promotes the PRC1 clustering, found several nucleoporins found in the nuclear pore complex (NPC). Similar to PHC2, depleting the nucleoporins also disrupted the DSB-induced gene silencing. We found that some of these nucleoporins, such as NUP107 and NUP43, which are members of the Y-complex of NPC, localize to DSB sites. The presence of nucleoporins and PHC2 at DSB regions was interdependent, suggesting that they act cooperatively in the DSB-induced gene silencing. We further found two structural components within NUP107 to be necessary for the transcriptional repression at DSBs: ATM/ Ataxia telangiectasia and Rad3-related-mediated phosphorylation at the Serine37 residue within the N-terminal disordered tail and the NUP133-binding surface at the C-terminus. These results provide a functional interplay among nucleoporins, ATM, and the Polycomb proteins in the DSB metabolism and underscore their emerging roles in genome stability maintenance.